Experiential Marketing Strategy to Increase Patient Visits at the General Dental Poly of Bunda Medika Pratama Clinic Tulungagung - Sri Wulandari, Meidya; Indasah; Agusta Dian Ellina (Universitas STRADA Indonesia, 2024)
The trend of patient visits at the Bunda Medika Clinic in 2018-2022 has decreased. This problem can be identified by knowing the causes of low dental poly services using an experiential marketing concept approach. The aim of this research is to analyze the influence of internal dental poly factors (human resources, medical and non-medical facilities, service rates) and patient expectations (customer expectations) on the patient experience (customer experience). Research with an observational analytical approach, using a cross sectional design. The research sample was general dental poly patients at the Bunda Medika Clinic in Tulungagung who had received treatment and met the inclusion criteria using a simple random sampling technique.